2001
DOI: 10.1152/jappl.2001.90.4.1359
|View full text |Cite
|
Sign up to set email alerts
|

Aged bone displays an increased responsiveness to low-intensity resistance exercise

Abstract: The ability of bone to respond to increased loading as a function of age was tested by use of three-point bending and histomorphometry. The hindlimbs of male Fischer 344 rats of three age groups (young = 4 mo, adult = 12 mo, and old = 22 mo; n = 10 per age group) were progressively overloaded by training the rats to depress a lever high on the side of a cage while wearing a weighted backpack. This squatlike movement required full extension of the hindlimbs. Exercised (Exer) rats performed 50 repetitions three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
33
0
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 34 publications
2
33
0
2
Order By: Relevance
“…In a recent study, we observed that tibial compression stimulated equal or greater cortical bone responses in 22-month old BALB/c mice compared to 7-month old mice [12]. Moreover, several (though not all [2], [3]) exercise studies in rodents reported that the skeletal benefits of exercise are not limited by age [4], [5], [6], [7], [8]. For example, 12 weeks of daily treadmill running [8] and 8 weeks of daily jumping [5] each produced significant increases in bone mass in 2-year old rats.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…In a recent study, we observed that tibial compression stimulated equal or greater cortical bone responses in 22-month old BALB/c mice compared to 7-month old mice [12]. Moreover, several (though not all [2], [3]) exercise studies in rodents reported that the skeletal benefits of exercise are not limited by age [4], [5], [6], [7], [8]. For example, 12 weeks of daily treadmill running [8] and 8 weeks of daily jumping [5] each produced significant increases in bone mass in 2-year old rats.…”
Section: Discussionmentioning
confidence: 92%
“…Exercise studies of young and aged rodents have demonstrated either reduced responsiveness in aged animals [2], [3], no difference between ages [4], [5], [6], or enhanced responsiveness in aged animals [7], [8]. Several studies that used extrinsic loading (e.g., tibial bending) reported reduced cortical responsiveness in aged turkeys [9], rats [10] and mice [11] compared to younger animals.…”
Section: Introductionmentioning
confidence: 99%
“…It is still controversial whether the responsiveness of the aged skeleton to mechanical loading is altered. It has been reported that the responsiveness of the aged skeleton is increased [17,18] , reduced [19,20] or unaffected [21,22] compared with the younger skeleton. Therefore, it is unclear whether reduced mechanoresponsiveness is involved in age-related bone loss.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, however, no published studies have been designed to assess the effects of two intensities of jump RE on weight-bearing cancellous bone. Additionally, there are very limited data about changes in cancellous bone remodeling, microarchitecture, and mechanical properties in skeletally mature animals with voluntary jump RE (3,37).…”
mentioning
confidence: 99%